Mailing Issues on Climate Change Policies - A Discussion of the GTAP-E Model - Hans Kremers; Peter Nijkamp; Shunli Wang (Tinbergen Institute, 2000)
After the Kyoto agreements the need has arisen to trace the implications ofvarious international environmentalstrategies. In this paper, we discuss relevant modelling issues ofincorporating important environmental policy measures in one ofthe popular applied general equilibrium models for internationaltrade, the so-called GTAP model. Special attention is paid to anextended version, the GTAP-E model, by addressing the question howto include the widely discussed instruments of InternationalEmission Trading, Joint Implementation, and Clean DevelopmentMechanisms. The paper will be concluded with some policy issues.
Keywords: 330; Klimaschutz; Internationale Umweltpolitik; Theorie